Regional Handball Referee Training in Kubu Raya - Eka Supriatna; Novi Yanti; Muhammad Fachrurrozi Bafadal; Rahmat Putra Perdana; Rubiyatno Rubiyatno (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2020)
Seeing the importance of the referee's role in leading the game, which the referee's role is essential in determining the match's results. This activity was held to provide the understanding and deepening of the handball refereeing material. The implementation of its practice in the field, strengthened by the granting of a regional referee license. There were 20 participants from each representative, especially the sub-districts in Kubu Raya district. The method used was training and mentoring by presenting competent speakers and instructors, especially in handball refereeing. As the results of the handball referee training activities, participants gained a better understanding of handball refereeing rules and practices and could practice them as an implementation of the knowledge they have acquired. The names of participants who have participated in this training were registered as regional licensed referees in the ABTI Management of West Kalimantan Province because they have been licensed at the regional level, which in the future can lead handball matches.